Contrasting impacts of competition on ecological and social trait evolution in songbirds - Drury,JP; Tobias,JA; Burns,KJ; Mason,NA; Shultz,AJ; Morlon,H (PLoS Biology, 2018)
Competition between closely related species has long been viewed as a powerful selective force that drives trait diversification, thereby generating phenotypic diversity over macroevolutionary timescales. However, although the impact of interspecific competition has been documented in a handful of iconic insular radiations, most previous studies have focused on traits involved in resource use, and few have examined the role of competition across large, continental radiations. Thus, the extent to which broad-scale patterns of phenotypic diversity are shaped by competition remain largely unclear, particularly for social traits. Here, we estimate the effect of competition between interacting lineages by applying new phylogenetic models that account for such interactions to an exceptionally complete dataset of resource-use traits and social signaling traits for the entire radiation of tanagers (Aves, Thraupidae), the largest family of songbirds. We find that interspecific competition strongly influences the evolution of traits involved in resource use, with a weaker effect on plumage signals, and very little effect on song. Our results provide compelling evidence that interspecific exploitative competition contributes to ecological trait diversification among coexisting species, even in a large continental radiation. In comparison, signal traits mediating mate choice and social competition seem to diversify under different evolutionary models, including rapid diversification in the allopatric stage of speciation.